Wastewater reuse in urban and peri-urban irrigation : an economic assessment of improved wastewater treatment, low-risk adaptations and risk awareness in Nairobi, Kenya - Mungatana, Eric D. (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.